Kesan faktor anak ke atas penyertaan tenaga buruh wanita berkahwin di Kedah: satu analisis model multinomial - Lim, Hock Eam; Mohd Mohaideen, Zalina (Universiti Utara Malaysia, 2003)
This study aims to measure the influence of children on the married women labour force participation in Kedah.This influence is divided into the number of children and child care cost. Based on the estimated multinomial logit model,the number of children is found to have significant and negative effects on the probability of work. The marginal effect of the number of children aged 0-1.4 years and 1.5-2.5 years in the highest. The effect of the number of children is also found much larger on probability of work as an employee,when compared to probability of work as an employer, and as a self-employed/family worker. Child care cost of the nursery does not have a significant negative impact,but, other child is found to be negative and significant.This negative impact is highest at RM300 and below per month.This implies that the government subsidies on child care cost (other than nursery) can help in increasing the married women labour force partcipation especially for those that have child care cost of RM300 and below per month. Nevertheless, the elasticity of labour force participation on this child care cost is inelastic.